2022
DOI: 10.1002/aid2.13305
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of stronger Neo‐Minophagen C in acute hepatitis after transarterial chemoembolization therapy for hepatomas

Abstract: Hepatitis after transarterial chemoembolization (TACE) is common. StrongerNeo-Minophagen C (SNMC) has demonstrated benefits in patients with hepatitis. We aimed to determine its usefulness in post-TACE hepatitis in patients with hepatomas. Overall, 60 patients with hepatomas who were treated with TACE were prospectively analyzed; of these, 30 patients underwent SNMC treatment after TACE. Daily serial changes in the liver function tests (serum levels of aspartate aminotransferase [AST], alanine aminotransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In this issue of Advances in Digestive Medicine, Huang et al conducted a prospective, randomized study to investigate the therapeutic effects of SNMC for patients with BCLC stage B HCC and underwent TACE. 15 The results showed that patients who received SNMC after TACE had a significantly lower serum bilirubin levels and shorter prothrombin time (PT) compared to those without SNMC therapy. They also had a lower rate of fever and nausea than their counterparts.…”
mentioning
confidence: 99%
“…In this issue of Advances in Digestive Medicine, Huang et al conducted a prospective, randomized study to investigate the therapeutic effects of SNMC for patients with BCLC stage B HCC and underwent TACE. 15 The results showed that patients who received SNMC after TACE had a significantly lower serum bilirubin levels and shorter prothrombin time (PT) compared to those without SNMC therapy. They also had a lower rate of fever and nausea than their counterparts.…”
mentioning
confidence: 99%